Electrical, photovoltaic and photosensitivity characteristics of p-ZnTe:N/CdTe:Mg/n-CdTe:I/GaAs for photodiode applications. (15th August 2017) - Yahia, I.S.; Farag, A.A.M.; Jafer, R.; Iqbal, Javed; Zahran, H.Y.; Chusnutdinow, S.; Wojtowicz, T.; Karczewski, G.
Abstract: In this work, heterojunctions of p-ZnTe:N/CdTe:Mg/ n -CdTe:I/GaAs for photovoltaic and photodiode application were grown epitaxially by using molecular beam system. Current-voltage profile of the heterojunction device was studied in dark and under various illumination intensities. The obtained photocurrent is found to depend on the light intensity. The main heterojunction parameters, such as shunt and series resistances, the barrier height and the ideality factor were extracted from the current-voltage profile using diverse methods at ambient temperature. Values of the barrier height and the series resistance were obtained from Cheung's functions. A large value of the series resistance causes the non-ideal characteristics of current–voltage measurements. The study of the current-voltage characteristics of high voltage region suggests a predominant space charge limited mechanism. Moderate values of short circuit current and open circuit voltage were obtained through a light intensity of 140 mW/cm 2, a current and voltages of 0.336 mA and 370 mV, respectively. The high photosensitivity and responsivity for the current under illumination condition suggests that the prepared heterojunction device could be employed as a photodiode sensor.